The role of inflammatory markers in Temporomandibular Myalgia: A systematic review - Elisabet Farré-Guasch; Jordi Tomàs Aliberas; Natalia Felipe Spada; Ralph de Vries; Engelbert A.J.M. Schulten; Frank Lobbezoo (Elsevier, 2023)
Approximately 10 % of the general population is affected by temporomandibular disorder (TMD) pain. Diagnosis of myogenous TMD pain (i.e., TM myalgia) may be challenging, while an adequate assessment of this pain is crucial to establish an adequate management strategy. We aim to analyze if there is a relation between inflammation and TM myalgia, and if we can identify and measure inflammatory markers in patients suffering from this condition. An electronic literature search was conducted from inception up to July 14 2022 through the databases PubMed, Cochrane Library, Web of Science, and Embase in collaboration with a medical information specialist. Studies on patients with masticatory muscle inflammation and/or pain were included. After a screening procedure, only nine full-text articles met the criteria for inclusion. In the included studies 9-131 patients showed TM myalgia, and presence of inflammation was reported with analysis of interleukines IL-1, IL-6, IL-10, tumor necrosis factor alpha, and prostaglandins from blood, saliva, and extracellular fluid of masseter muscle using microdialysis. Our results contributed to the identification of the relation between inflammation and TM myalgia and established that measurement of inflammatory cytokines may be a valid diagnostic tool, which is an essential step towards finding a better treatment.